Ipilimumab in pretreated patients with unresectable or metastatic cutaneous, uveal and mucosal melanoma. Issue 1 (7th July 2014) - Alexander, Marliese; Mellor, James D; McArthur, Grant; Kee, Damien
Abstract: Objectives: To evaluate the efficacy and tolerability of ipilimumab in an Australian clinical setting, and to assess the association of response with melanoma subtype, BRAF mutation status, absolute lymphocyte count and incidence of serious immune‐related adverse events (AEs). Design, setting and participants: Retrospective review of patients with unresectable or metastatic melanoma treated with ipilimumab at an Australian oncology centre between July 2010 and April 2012. Main outcome measures: Overall survival (OS), progression‐free survival (PFS), incidence and severity of AEs. Results: 104 patients were retrospectively followed for a median of 7 months (range 0–30 months). Median OS was 9.6 months (95% CI, 6.6–12.4), and median PFS was 3.0 months (95% CI, 2.7–3.4). The 1‐ and 2‐year survival rates were 42% (95% CI, 32%–52%) and 18% (95% CI, 9%–30%), respectively. Median OS for patients with non‐cutaneous (mucosal and uveal) melanomas was almost half that of patients with cutaneous melanoma: 5.8 months (95% CI, 2.8–12.4) v 11.7 months (95% CI, 7.1–13.8); P = 0.11. Raised absolute lymphocyte count was associated with increased PFS ( P ≤ 0.005 at all measured time points) but not with OS ( P > 0.15). Sex, age, brain metastases, BRAF mutation status, incidence of severe immune‐related AEs and baseline lactate dehydrogenase levels did not affect OS or PFS ( P > 0.05). Eighteen of 104 patients experienced serious AEs (≥ grade 3), including two treatment‐related deaths. Conclusion: In an Australian clinical practice setting, ipilimumab achieved efficacy and tolerability measures similar to those reported in clinical trials. The frequency and severity of ipilimumab‐related AEs (including death) are notable, and treatment should occur under the supervision of an experienced clinical team.